2013
DOI: 10.1371/journal.pone.0068756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Larvae Treated with Mixed Biopesticide Bacillus thuringiensis - Abamectin on Sex Pheromone Communication System in Cotton Bollworm, Helicoverpa armigera

Abstract: Third instar larvae of the cotton bollworm (Helicoverpa armigera) were reared with artificial diet containing a Bacillus thuringiensis - abamectin (BtA) biopesticide mixture that resulted in 20% mortality (LD20). The adult male survivors from larvae treated with BtA exhibited a higher percentage of “orientation” than control males but lower percentages of “approaching” and “landing” in wind tunnel bioassays. Adult female survivors from larvae treated with BtA produced higher sex pheromone titers and displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…Sun et al (2002) studied the S. litura sex pheromone mating system and found that the sex pheromone components, Z9, E11-14:Ac and Z9, E12-14;Ac, which were collected from female S. litura of Shanghai, China, had a ratio of 100:27; however, Tamaki & Yushima (1974) studied S. litura in Japan and found that the proportion of the same two components was 9:1. These variations could have been caused by various natural factors, including food (Groot et al, 2008), age, mating status, and environmental conditions such as photoperiod, temperature (Ono, 1994;Ding et al, 2014) and the use of pesticides (Trimble et al, 2004;Wei et al, 2004;Shen et al, 2013), which are factors with known effects on the female sex pheromone biosynthesis pathway. Accordingly, conspecific males adapt to these biotic and abiotic factors (Jarriault et al, 2009;Groot et al, 2010;Barrozo et al, 2011;Deisig et al, 2012;Rabhi et al, 2014Rabhi et al, , 2016Schlager et al, 2015), which leads to the modulation of odour-driven behaviour through the concerted regulation of odour maps (Saveer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2002) studied the S. litura sex pheromone mating system and found that the sex pheromone components, Z9, E11-14:Ac and Z9, E12-14;Ac, which were collected from female S. litura of Shanghai, China, had a ratio of 100:27; however, Tamaki & Yushima (1974) studied S. litura in Japan and found that the proportion of the same two components was 9:1. These variations could have been caused by various natural factors, including food (Groot et al, 2008), age, mating status, and environmental conditions such as photoperiod, temperature (Ono, 1994;Ding et al, 2014) and the use of pesticides (Trimble et al, 2004;Wei et al, 2004;Shen et al, 2013), which are factors with known effects on the female sex pheromone biosynthesis pathway. Accordingly, conspecific males adapt to these biotic and abiotic factors (Jarriault et al, 2009;Groot et al, 2010;Barrozo et al, 2011;Deisig et al, 2012;Rabhi et al, 2014Rabhi et al, , 2016Schlager et al, 2015), which leads to the modulation of odour-driven behaviour through the concerted regulation of odour maps (Saveer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Successful pest control depends on the prolongation of the efficacy of insecticides. Therefore the assessment of the sublethal effects of an insecticide is important, and several studies on the sublethal effects of insecticides have been reported for a number of lepidopteran pests including Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae) (Guo et al 2013;Wang et al 2011;Yin et al 2008), Helicoverpa armigera (Hübner), S. littoralis and Mamestra brassicae (Linnaeus) (Lepidoptera: Noctuidae) (El-Sheikh 2015; Moustafa et al 2016;Parsaeyan et al 2013;Shen et al 2013). The disturbance could reflect protective physiological responses such as the increment of cytochrome P450-dependent monooxygenases, carboxylesterases (CarE), and/or glutathione S-transferases (GST) that play important roles in insecticide metabolism (Yu 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The calling curves of the insecticide treatments for the most part fell within the boundaries of the acetone control curves, so the shift in calling period with thiacloprid was not as remarkable as the effect on the amount of calling. A detrimental effect of sublethal insecticide on calling behavior has been observed in other moth species with pyrethroid (Haynes and Baker 1985;Clark and Haynes 1992a;Yang and Du 2003;Shen et al 2013;Quan et al 2016) and organophosphate insecticides (Trimble et al 2004).…”
Section: Discussionmentioning
confidence: 93%